The Dating of Nogaichik Barrow and the Cultural Identity of the Elite Burials of the North Pontic Region - Mordvintseva, Valentina (Anabasis. Studia Classica et Orientalia, 2012)
The dating of the Nogaīchik Barrow for many years is the subject of debates and discussion. Some scholars date it to the late 1st – early second 2nd century AD. However, the burial contained objects which are characteristic for the Late Hellenistic period, mainly for the 1st c. BC. The recently undertaken dendrochronological analysis of a wooden stand from the burial and the 14 С analysis of the bones of the dead also provide the same date. To the same chronological period belong some other female ostentatious burials from the Lower Volga, Lower Don and the Kuban. This group is not homogeneous. There are features that unite them (a number of gold jewellery, precious drinking vessels, mirrors) and on which they differ (form and construction of the burial constructions; presence or absence of the animal bones in the grave, etc.). The local isolation of the Nogaīchik Barrow from any burial ground does not allow one to correlate it reliably with any particular culture. At the same time, some specific features of the burial rite (concentration of grave goods on the right side along the body, hands were put in bowls) and specific types of burial goods (a ceramic jug, zoomorphic pendants, torque, brooch-pin, foot-rings), indicate its proximity with the archaeological culture of the Kuban region of the Hellenistic period. The appearance of particularly rich burials in the archaeological cultures of the Lower Volga, the Lower Don and the Kuban in the I c. BC could be associated with the increased centralization of social elites, partly as a result of the foreign policy of King of Pontus Mithradates the VI Eupator.